Effects of Different Anticoagulants on Determination of Erythrocyte Glutathione Peroxidase - Hussein, Kamal S. M. (Acta Vet Scand, 2021)
Glutathione peroxidase (GSH-Px) was determined in whole blood from cows, goats and horses using cumenehydroperoxide as substrate. Heparin was found to be the most suitable anticoagulant. The highest activities of GSH-Px were found with high concentrations of heparin in the blood samples (1000 and 1250 IU/ml of blood). Sodium fluoride and especially EDTA and sodium citrate gave lower activities of the enzyme. Storage of the blood samples at room temperature (~20°C) or in a refrigerator (~5°C) for 3 days resulted in significantly lower activities of the enzyme, especially in horse blood.